MATHEMATICS TEXTBOOK ANALYSIS: A STUDY ON RECOMMENDED MATHEMATICS TEXTBOOKS IN SCHOOL USE IN SOUTHWESTERN STATES OF NIGERIA - Afolabi Samson Sunday (European Scientific Journal, ESJ, 2014)
Textbook has been emphasized to be the most important tool in the teaching-learning process of Mathematics. It has been identified as one of the factors affecting students‘ learning outcomes. Few researches available on textbook rarely consider textbook analysis. Many of such have often reported paucity of research on textbooks and further research is thus recommended. This study is one of those on content analysis of Mathematics textbook. The study has provided empirical evidence on the relevance, suitability and adequacy of some recommended Mathematics textbooks in Southwestern Nigeria. Eleven features in the textbooks were analysed directly by the users (teachers). Mathematics teachers were purposively selected from two randomly selected public secondary schools in each of the senatorial districts of all the six states in southwestern geopolitical zone. The study comprised 117 Mathematics teachers as the total respondents from the 36 public secondary schools that were selected for the study. The comparison of the features was in line with the expectations of the Senior Secondary School National Mathematics Curriculum. The features were well provided for in the textbooks. The books were relevant, suitable and adequate in their provisions and capable of bringing forth desirable learning outcomes. The textbooks however, need further provision of Students‘ Workbook, Teachers‘ Guide, progressive hierarchy of tasks, multiple and attractive colours. The establishment of Textbook Standard Content Review Panel (TSCRP) was recommended to approve textbooks for school use after proper screening by this body. Years for reprint, re-editing were to be recommended by the committee or panel.